An extensive analysis of numerical ship self-propulsion prediction via a coupled BEM/RANS approach. (June 2017) - Gaggero, Stefano; Villa, Diego; Viviani, Michele
Highlights: The prediction of self-propulsion condition is very demanding; the proposed method has been designed to overcome this issue. The RANS/BEM coupling approach makes the self-propulsion simulations daily affordable in an early ship design stage. This approach has been applied to the KCS test case to investigate its strength and weakness. An extensive numerical validations with available experimental measurements has been carry out. Each source of error has been investigated comparing also with a full RANS approach. Abstract: The paper deals with the self-propulsion problem, i.e. the solution of the flow around the hull that advances at uniform speed due to the action of its own propeller. A coupled BEM/RANS approach, previously proposed for a simpler case with only rudder and propeller, has been extensively analysed to highlight the strength and the weakness of the method. The proposed analyses consider the influence of different turbulence modelling, the role of the interpolating algorithm for the inclusion of body forces into the RANS domain, a mesh and simulation time step sensitivity study and the influence of the extrapolation procedure for the definition of the effective wake to the propeller in the light of the lightest and the most affordable computational setup for daily accurate calculations. At first, the well-known Kriso Container Ship (KCS) test case is considered. This ship has been widely investigated in the context of different research projects and a large amount of data (both measurements and numerical calculations) is available to validate the solution approach and to highlight the benefits, as well as the weaknesses, of the proposed coupled BEM/RANS approach versus established but computationally demanding calculations based only on RANS simulations. Once the approach has been developed and validated via the KCS test case, calculations have been repeated in the case of completely different ships, in order to evaluate its general applicability and to test the robustness and the reliability of the proposed procedure.